The Impact of Artificial Intelligence (AI) Implementation on Students’ Mindset in The Era of The Fourth Industrial Revolution - Rinna Yuanita Kasenda; Khoirul A. R. Yoyatan; Balgis Sakina; Raikokimmi V. R. Mamangkey; Kichiro P. P. Kosegeran (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Background: The ongoing Fourth Industrial Revolution has brought significant impacts across various aspects of life, particularly in technological development. One of the most influential technologies is Artificial Intelligence (AI), which is known for its ability to solve problems more efficiently. Objective: For university students, the implementation of AI plays an important role in supporting learning processes, enhancing analytical skills, and facilitating access to information. Methods: This study employs a literature review method by examining various academic sources related to the use of AI in higher education. Results: The findings indicate that AI provides positive impacts on students’ mindsets, including increased creativity, learning effectiveness, and critical-thinking abilities. However, potential negative effects were also identified, such as decreased intellectual independence and excessive reliance on technology. Conclusion: Therefore, appropriate strategies for AI utilization are required to ensure that students do not merely become passive users but instead can maximize the technology to develop a critical, innovative, and competitive mindset.